A study of the teaching of reading in Grade 1 in the Caprivi region, Namibia - Nzwala, Kenneth (Rhodes University, Faculty of Education, Department of Education, 2007)
This study was conducted in order to understand how Grade 1 teachers teach reading in mother tongue with a focus, firstly, on teacher beliefs and how such beliefs influence teachers' practice, and secondly, on the methods they use to teach reading. The study was carried out in the Caprivi Region of Namibia. It took the form of an interpretive case study. Three schools were selected for study: one urban, one peri-urban and one rural. The purpose of this sampling was to consider the influence of context on teachers' practice. The data was gathered by using semi-structured interviews with open ended questions, as well as lesson observations and stimulated recall with the individual teachers after every lesson. This was important in order to have clarity on areas that were not clear during lesson presentations. The key findings are that the teachers I studied taught reading without using books, and there was an absence of shared reading with the learners. Other key findings are: teachers had great love for stories; they had a problem of language, and had no proper understanding of the concept 'literacy'.
Keywords: Reading (Primary) -- Namibia Teachers -- Attitudes -- Namibia; Teaching -- Namibia